Snalazenje u politici zastite na radu Europske Unije : vodic za sindikate - Jacobsen, Lone; Kempa, Viktor; Vogel, Laurent (Brussels, 2009)
"This handbook aims to give an overview of the EU institutions and procedures involved in regulating health and safety at work, and the role of trade unions in relation to it. Depending on where their interests lie and what they already know about a given issue, readers can choose to explore the structure and organisation of the EU, ways in which trade unions can have an influence, or specific national examples.